Performing balanced aspirations through identity capital: A case study of Chinese Ivy League influencers on RedNote - Chen, Siyu; Jiang, Xinxin (Journal of consumer culture, 2025)
While studies on Chinese social influencers are proliferating, the dynamics of emerging elite influencers remain underexplored. Through a Bourdieusian lens, we explore how “Ivy League girls”—a group of female Chinese influencers from elite backgrounds studying at prestigious Western universities—curate their online personae by showcasing balanced aspirations on RedNote, a popular social media and e-commerce platform in China. Drawing on digital ethnography, we examine how these privileged influencers mobilize various forms of identity capital to navigate the tensions between class, gender, and nation through careful negotiations of glamour and grit, Chineseness and cosmopolitanism, and empowerment and conformity. These balanced performances reveal the constraints imposed by China’s market-state complex in the digital era and their agency in navigating cultural tensions in self-representations. Through the lens of aspiration, we offer critical insights into how the changing mechanism of social distinction shape the self-branding strategies of elite influencers within an attention-driven, globalized economy. Analyzing how elite influencers leverage their diverse portfolio of resources, this study advances our understanding of the reproduction of privilege in the digital sphere and beyond.